Elucidating the mechanisms behind thermoelectric power factor enhancement of poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) flexible films. (July 2018) - Bharti, Meetu; Singh, Ajay; Samanta, Soumen; Debnath, A.K.; Marumoto, Kazuhiro; Aswal, D.K.; Muthe, K.P.; Gadkari, S.C.
Abstract: Conducting polymers that have shown their potential in flexible electronics and sensorics for the last one decade can be looked upon as promising materials for room temperature thermoelectric applications. Among all the existing popular conducting polymers, poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is being widely studied because of its extraordinary high electrical conductivity and environmental stability. This article explains the possible mechanisms behind power factor enhancement of solvent-mixed flexible PEDOT:PSS films. The films drop-casted on polyimide sheets by using both pristine and organic solvent (dimethyl sulphoxide i.e. DMSO) pre-mixed solutions were optimized for both annealing temperature and solvent concentrations. The detailed characterization of these films suggested that PSS was detached from PEDOT:PSS after DMSO addition. Selective eviction of PSS from typical core-shell structure of PEDOT:PSS not only caused conformational change in PEDOT chains from benzoid (coiled structure) to quinoid (linear structure) but also re-arranged PSS in more stretched form. Such a modification of the chemical structure caused improvement in power factor mainly due to enhanced charge carriers' mobility rather than increased doping/carrier concentration. A flexible thermoelectric generator consisting of an array of thirty elements was also fabricated by drop-casting DMSO-mixed PEDOT:PSS solution through a patterned mask. This array resulted in an output voltage of ∼17.6 mV under a temperature gradient of 80 °C. Graphical abstract: Dominant mechanism for enhancement of power factor in DMSO-mixed PEDOT:PSS films is attributed to the ordering of both PEDOT and PSS chains that caused improvement in charge carrier mobility. Highlights: Improvement of two orders of magnitude in thermoelectric power factor through simple treatment by the organic solvent. Detailed investigation by optimizing annealing temperature as well as dopant/solvent concentration. Drop-casted films on flexible polyimide (Kapton) sheets being favourable for wearable thermoelectrics. Fabrication of a prototype flexible and wearable thermoelectric power generator. Understanding the mechanism of improvement in thermoelectric performance mainly through chain alignment.